2018
DOI: 10.1090/jams/906
|View full text |Cite
|
Sign up to set email alerts
|

A random Schrödinger operator associated with the Vertex Reinforced Jump Process on infinite graphs

Abstract: This paper concerns the Vertex reinforced jump process (VRJP), the Edge reinforced random walk (ERRW) and their link with a random Schrödinger operator. On infinite graphs, we define a 1-dependent random potential β extending that defined in [20] on finite graphs, and consider its associated random Schrödinger operator H β . We construct a random function ψ as a limit of martingales, such that ψ = 0 when the VRJP is recurrent, and ψ is a positive generalized eigenfunction of the random Schrödinger operator wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
134
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(138 citation statements)
references
References 20 publications
4
134
0
Order By: Relevance
“…We should mention that a similar phase transition was conjectured for linearly edge-reinforced random walks (ERRW) on Z d in the eighties [7], and was first proved on regular trees in [16]. Only recently, the phase transition recurrence/transience on Z d , d ≥ 3, was established in [18,1,9], see also [19]. However, techniques developed for ERRW do not apply to ORRW, in particular because exchangeability does not hold.…”
mentioning
confidence: 87%
“…We should mention that a similar phase transition was conjectured for linearly edge-reinforced random walks (ERRW) on Z d in the eighties [7], and was first proved on regular trees in [16]. Only recently, the phase transition recurrence/transience on Z d , d ≥ 3, was established in [18,1,9], see also [19]. However, techniques developed for ERRW do not apply to ORRW, in particular because exchangeability does not hold.…”
mentioning
confidence: 87%
“…Consistency of the law of β was first observed by Sabot and Zeng in [SZ15]; see also Lemma 2.4 in [DMR17]. By Kolmogorov's consistency theorem, there is a probability space…”
Section: Results In Infinite Volumementioning
confidence: 90%
“…More recently Sabot, Tarrès, and Zeng developed further the random Schrödinger operator interpretation [STZ17] [SZ15]. In particular they derived the explicit law for the random potential, and constructed two families of martingales in discrete time.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…See [1] for a discussion and precise statements. It has also been shown that the linearly edge-reinforced random walk (ERRW) with constant initial weights is recurrent in two dimensions [19,24], but the recurrence of the VRJP for all initial rates was an open problem until the present work. The relation between the ERRW and VRJP is discussed below.…”
Section: Introduction and Resultsmentioning
confidence: 93%
“…The analogue of Theorem 1.1 for the ERRW with constant initial weights was established in [19,24], but not for the VRJP. Mermin-Wagner type theorems have also been proven for the ERRW in one and two dimensions [18,19].…”
Section: Hyperbolic Mermin-wagner Theoremmentioning
confidence: 99%